Small steps, strong shield: directly measured, moderate physical activity in 65 361 adults is associated with significant protective effects from severe COVID-19 outcomes. Issue 10 (9th February 2022) - Steenkamp, Lizelle; Saggers, Robin Terence; Bandini, Rossella; Stranges, Saverio; Choi, Yun-Hee; Thornton, Jane S; Hendrie, Simon; Patel, Deepak; Rabinowitz, Shannon; Patricios, Jon
Abstract : Objective: To determine the association between directly measured physical activity and hospitalisation, intensive care unit (ICU) admission, ventilation and mortality rates in patients with a confirmed diagnosis of COVID-19. Methods: Directly measured physical activity data from 65 361 adult patients with a COVID-19 diagnosis from 19 March 2020 to 30 June 2021, were grouped by activity level: low (<60 min/week), moderate (60–149 min/week) and high activity (≥150 min/week). The association of physical activity levels and the risk of adverse outcomes was analysed using modified Poisson regression. We accounted for demographics and comorbidities including conditions known to influence COVID-19 outcomes, as well as patient complexity as measured by the Johns Hopkins Adjusted Clinical Group system. The regression approach was further validated with a Bayesian network model built off a directed acyclic graph. Results: High physical activity was associated with lower rates of hospitalisation (risk ratio, RR 0.66, 95% CI 0.63 to 0.70), ICU admission (RR 0.59, 95% CI 0.52 to 0.66), ventilation (RR 0.55, 95% CI 0.47 to 0.64) and death (RR 0.58, 95% CI 0.50 to 0.68) due to COVID-19 than those who engaged in low physical activity. Moderate physical activity also was associated with lower rates of hospitalisation (RR 0.87, 95% CI 0.82 to 0.91), admission to ICU (RR 0.80, 95% CI 0.71 to 0.89), ventilation (RR 0.73, 95% CI 0.62 to 0.84) and death (RR 0.79, 95% CI 0.69 to 0.91). Conclusions: Adults with high and moderate physical activity levels had significantly better outcomes than those with low activity when contracting COVID-19. The apparent protective effects of regular physical activity extended to those with concomitant chronic medical conditions.